A arte de andar nas ruas de Brasília - Sophia Beal (Estudos de Literatura Brasileira Contemporânea)
As Certeauargues, walking divulges something intimate: the personalized use ofthe city. In literature from Brasília, walking divulges pleasure seeking, risk taking,and attempts to personalize a city designed more for cars than pedestrians.Walking in Brasília issomewhat of a paradox. What is the role of the pedestrian ina city designed for car travel and shaped like an airplane? This series of poems,crônicas, contos, and songs (by Nicolas Behr, Aborto Elétrico, Capital Inicial,Legião Urbana, GOG, José RezendeJr., Pedro Biondi, Liziane Guazina, FernandaBarreto, and Augusto Rodrigues) overturn Brasília‘s top-down origins andorganization, suggesting that current residents as they walk around the city intheir daily lives—are creating and transforming the capital in significant ways.